THE PORTRAYAL OF HEROISM IN THE ORSON SCOTT CARD’S NOVEL ENDER’S GAME - Rosianah, Rosianah; Kuncara, Singgih Daru; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2018)
ABSTRACT This research discussed about the portrayal of heroism in the Orson Scott Card’s novel Ender's Game, based on Joseph Campbell’s hero’s journey. This research has two objectives, the first is to reveal the journey of Ender to become a hero and the second is to reveal hero traits in Ender’s character that appear during his journey. This study used qualitative approach. The subject of this study is novel by Orson Scott Card entitle Ender’s Game. The data were some sentences and utterances showing the hero’s Journey and hero traits. To obtain trustworthiness, the writer used triangulation technique. The writer found that the hero in his journey passed thirteen stages among seventeen stages of hero’s Journey, namely Call to adventure, Refusal of the call, Supernatural aid, Crossing the first threshold, Belly of the whale, Road of trials, Meeting with the goddess, Atonement with Father, Apotheosis, Ultimate boon, Refusal of the call, Crossing the threshold, Master of the two worlds, and Freedom to live. Three stages were absent, Woman temptress, Magic flight, and Rescue from within. In every phase Ender as the main character showed traits that indicate he is a hero. He showed twelve hero traits, there are; Courage, Virtuosity, Sacrifice, Determination, Focus, Compassion, Perseverance, Dedicate, Honesty, Loyalty, Conviction, and Wisdom. Keywords: hero, hero’s journey, traits ABSTRAK Penelitian ini membahas tentang penggambaran kepahlawanan dalam novel Ender’s Game karya Orson Scott Card. Terdapat dua objek penelitian, pertama mengungkapkan perjalanan Ender untuk menjadi seorang pahlawan, dan objek kedua mengungkapan ciri-ciri pahlawan yang muncul pada karakter Ender dalam perjalannya . Subjek dalam penelitian ini adalah novel karya Orson Scott Card yang berjudul Ender’s Game. Data dalam penelitian ini adalah kalimat-kalimat dan ucapan yang menunjukkan “hero’s Journey” dan ciri-ciri pahlawan. Untuk mendapatkan kepercayaan, penulis menggunakan teknik triangulasi. Penulis menemukan bahwa Ender sebagai pahlawan dalam perjalanannya melewati tiga belas tahap di antara tujuh belas tahap perjalanan pahlawan, yaitu Call to adventure, Refusal of the call, Supernatural aid, Crossing the first threshold, Belly of the whale, Road of trials, Meeting with the goddess, Atonement with Father, Apotheosis, Ultimate boon, Refusal of the call, Crossing the threshold, Master of the two worlds, and Freedom to live. Terdapat tiga tahap yang tidak muncul dalam novel, yaitu, Woman as temptress, Magic flight, and Rescue from within. Di setiap tahap Ender sebagai karakter utama menunjukkan ciri-ciri yang menunjukkan bahwa dia adalah pahlawan. Dia menunjukkan dua belas ciri-ciri pahlawan, yaitu; Courage, Virtuosity, Sacrifice, Determination, Focus, Compassion, Perseverance, Dedicate, Honesty, Loyalty, Conviction, dan Wisdom. Kata kunci: pahlawan, perjalanan pahlawan, ciri-ciri